Enhancing the Academic Writing of EFL Learners: An Analysis of Effective Strategies through Meta-Synthesis - Fahrus Zaman Fadhly (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This study presents a meta-synthesis analysis of the challenges faced by English as a Foreign Language (EFL) learners in composing academic writing (AW). A comprehensive literature review was conducted to identify relevant studies on EFL learners' difficulties in AW, leading to the inclusion of 25 articles in the final analysis. The selected articles were systematically analyzed and synthesized to identify common themes and patterns related to the difficulties EFL learners face in AW. The findings revealed five major categories of challenges: including linguistic difficulties, organizational and coherence problems, cultural and sociocultural factors, feedback and revision, and motivation and self-efficacy. Based on the meta-synthesis, recommendations for teaching and learning practices are provided, as well as directions for future research in the area of EFL composition. By understanding the challenges faced by EFL learners in composition, educators can develop targeted interventions and support strategies to facilitate their students' progress and success in composing texts.